4CPS-059 Linezolid dosing in patients with liver cirrhosis: standard dosing risks' toxicity. (2nd March 2018) - Luque, S; Echeverria-Esnal, D; Martinez-Casanova, J; Gonzalez-Colominas, E; Fernandez-Sala, X; Barcelo, J; Muñoz, R; Alvarez-Lerma, F; Grau, S
Abstract : Background: Linezolid is used at a standard dose of 600 mg/12 hours regardless of renal or hepatic function but very little data concerning its pharmacokinetics (PK), efficacy and safety in patients with liver cirrhosis is available. Purpose: The objectives were to describe the PK, efficacy and safety of linezolid in cirrhotic patients. Material and methods: A prospective case-control 1:1 study conducted between January 2015 to June 2017. Cases were all cirrhotic patients treated with linezolid undergoing therapeutic drug monitoring (TDM). Controls were matched by age, actual bodyweight, comorbidities, renal function (glomerular filtration rate (GFR)) and severity. Subtherapeutic linezolid concentrations were defined as a through (Cmin) concentration <2 mg/L and supratherapeutic as a Cmin >10 mg/L. Thrombocytopaenia was defined as a decrease in platelet count to <75% and anaemia as an ≥2 g/dL decrease in haemoglobin, both from baseline. Data are described as the mean± (standard deviation SD). The Student's t-test or Mann–Whitney U-test for continuous variables and the Chi-square or Fisher's exact test for dichotomous variables were used. Results: Fifty-two patients were included. Mean age: 62 (±11. 9) years, males 66. 1%, without differences in baseline demographic and clinical characteristics excepting for low baseline platelet count (57.7% vs. 26.9%, p=0.025). Conclusion: Cirrhotic patients were more likely to have supratherapeutic concentrations of linezolid and a lower final platelet count, probably due to reduced non-renal clearance. Linezolid showed a good clinical response rate with no differences between patients with and without cirrhosis. These results question the use of standard doses of linezolid to this population and highlight the need to perform TDM to reduce toxicity. No conflict of interest